2022
DOI: 10.1136/jmg-2022-108502
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applicability of the Polygenic Risk Score for breast cancer risk prediction in familial cases

Abstract: BackgroundCommon low-risk variants are presently not used to guide clinical management of familial breast cancer (BC). We explored the additive impact of a 313-variant-based Polygenic Risk Score (PRS313) relative to standard gene testing in non-BRCA1/2 Dutch BC families.MethodsWe included 3918 BC cases from 3492 Dutch non-BRCA1/2 BC families and 3474 Dutch population controls. The association of the standardised PRS313 with BC was estimated using a logistic regression model, adjusted for pedigree-based family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In a Dutch study, the impact of incorporating the PRS into risk calculations for 1331 non-BRCA1/2 carriers was investigated regarding screening procedures aligned with Dutch IKNL [56], UK NICE [57], and US NCCN [58] BC screening guidelines. The results revealed clinically significant shifts in 32.4%, 36.0%, and 25.7% of individuals (with 30% BC lifetime risk cut-off levels based on the IKNL and NICE BC screening guidelines) [59].…”
Section: Discussionmentioning
confidence: 97%
“…In a Dutch study, the impact of incorporating the PRS into risk calculations for 1331 non-BRCA1/2 carriers was investigated regarding screening procedures aligned with Dutch IKNL [56], UK NICE [57], and US NCCN [58] BC screening guidelines. The results revealed clinically significant shifts in 32.4%, 36.0%, and 25.7% of individuals (with 30% BC lifetime risk cut-off levels based on the IKNL and NICE BC screening guidelines) [59].…”
Section: Discussionmentioning
confidence: 97%
“…Clinical recommendations changed for 31·5 % (58/184) of these women when applying the 20 % eLTR threshold, 15·8 % (29/184) when applying the 30 % eLTR threshold, and 22·4 % (41/183) when applying the 5 % e10YR threshold. Lakeman et al recently described that integrating PRS 313 data in CanRisk-based risk prediction affects clinical recommendations for 26·8 % (635/2369) of women tested non-informative when applying the 20 % eLTR threshold, and 7·1 % (167/2369) when applying the 30 % eLTR threshold [ 19 ]. This is similar to the effects observed in our investigation using the PRS risk estimation model (20 % eLTR: 26·1 %, 48/184; 30 % eLTR: 12·0 %, 22/184, Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, risk effects conferred by CHEK2 and 77 common variants acted multiplicatively [ 16 ] and more recently, two studies including variant status, individual clinical variables and PRS showed meaningful shifts in LTBCR in CHEK2 carriers regardless of a family history of BC [ 24 , 25 ]. In the familial cancer setting, one study on BC risk prediction of non- BRCA1/2 Dutch families showed that the addition of PRS 313 changed clinical management in 58 % of the CHEK2 carriers [ 26 ]. However, a recent study found linkage between two SNPs located on the 22nd chromosome (chr22:29203724:C/T and chr22:29551872:A/G) and the CHEK2 c.1100delC variant, and therefore using PRS 313 would result in an overestimation of BC risk in heterozygotes.…”
Section: Introductionmentioning
confidence: 99%